Relationships Between Thyroid Hormones, Insulin-Like Growth Factor-1 and Antioxidant Levels in Hypothalamic Amenorrhea and Impact on Bone Metabolism - Mancini, Antonio; Vergani, Edoardo; Bruno, Carmine; Barini, Angelina; Silvestrini, Andrea; Meucci, Elisabetta; Messana, Calogero; Romualdi, Daniela; Apa, Rosanna; Lanzone, Antonio (Hormone and Metabolic Research, 2019)
Reduced bone mineral density (BMD) in Functional Hypothalamic Amenorrhea (FHA) is mainly related to hypoestrogenism, but other hormonal derangement (reduced conversion of T4–T3 and GH resistance) can play a role. These hormones are involved in antioxidant systems regulation. We evaluated the impact of hormonal alterations, with special focus on low T3 and IGF-1 levels, on antioxidant systems as a link with osteoporosis in FHA. Forty-three FHA patients, 15–34 years, with BMI range 17.3–23.4 kg/m2, were divided in 2 groups according to fT3 levels; group A (n=22), low fT3 (<2.4 pg/ml) and group B (n=21), normal fT3 (≥ 2.4 pg/ml). We evaluated hormonal parameters (fT3, fT4, TSH, IGF-1, FSH, LH, estradiol, DHEAS, testosterone, cortisol), bone metabolism (calcium, phosphorus, 25-OH Vitamin D, PTH, β-crosslaps, bone alkaline phosphatase) and total antioxidant capacity (TAC), expressed as LAG (latency time in radical species appearance using spectrophotometric method). BMD was assessed by DEXA. Group A patients exhibited significantly lower levels of IGF-1 (159.76±14.79 vs. 220.05±15.25 ng/ml) and osteocalcin (17.51±1.14 vs. 21.49±1.56 ng/ml); LAG values were significantly higher in A (66.33±1.74 s) vs. B (54.62±1.74 s). A significant direct correlation was found between both IGF-1 and fT3 with osteocalcin (r²=0.22, p=0.0049 and r²=0.34, p=0.0001, respectively). No difference in LAG between groups according to IGF-1 were found. These data show a correlation between altered bone turnover and low fT3, which is highly prevalent in FHA. Low fT3 levels may contribute to reduced BMD. Oxidative stress could be the link underlying different bone turnover pattern and endocrine dysfunction in FHA.
Keywords: amenorrhea; osteoporosis; non-thyroidal illness; osteocalcin; antioxidants